Coping With the COVID-19 Pandemic: Examining Gender Differences in Stress and Mental Health Among University Students - Prowse, Rebecca; Sherratt, Frances; Abizaid, Alfonso; Gabrys, Robert L.; Hellemans, Kim G. C.; Patterson, Zachary R.; McQuaid, Robyn J. (Frontiers in Psychiatry, 2021)
The COVID-19 pandemic has imposed a wide variety of unprecedented challenges, many of which appear to be disproportionately affecting the mental health and well-being of young adults. While there is evidence to suggest university students experience high rates of mental health disorders, less is known about the specific impacts of the COVID-19 pandemic on student mental health and how they are coping with this stress. To address this gap, we conducted an online study among undergraduate students (n = 366) to examine the impact of the COVID-19 pandemic on academics, social isolation, and mental health, as well as the extent to which they have been implementing a variety of coping strategies. The pandemic had a more pronounced negative effect on female students’ academics, social isolation, stress and mental health compared to male counterparts. Moreover, for females, frequent use of social media as a coping mechanism was associated with greater perceived negative impacts on their academic performance and stress levels, compared to males. However, frequent social media use related to similar negative mental health effects for both males and females. While male and female students both reported using substances to cope, for males the use of cannabis was associated with greater negative impacts on academic outcomes, stress and mental health compared to females. These findings highlight the need for adequate student support services across the post-secondary sector, and point to the importance of gender informed interventions to address the impacts of the COVID-19 pandemic.